PCSK9 Plasma Concentrations Are Independent of GFR and Do Not Predict Cardiovascular Events in Patients with Decreased GFR - Rogačev, Kyrill; Kleber, Marcus E.; März, Winfried (PLOS ONE, 2016)
Background Impaired renal function causes dyslipidemia that contributes to elevated cardiovascular risk in patients with chronic kidney disease (CKD). The proprotein convertase subtilisin/kexin type 9 (PCSK9) is a regulator of the LDL receptor and plasma cholesterol concentrations. Its relationship to kidney function and cardiovascular events in patients with reduced glomerular filtration rate (GFR) has not been explored. Methods Lipid parameters including PCSK9 were measured in two independent cohorts. CARE FOR HOMe (Cardiovascular and Renal Outcome in CKD 2-4 Patients - The Forth Homburg evaluation) enrolled 443 patients with reduced GFR (between 90 and 15 ml/min/1.73 m2) referred for nephrological care that were prospectively followed for the occurrence of a composite cardiovascular endpoint. As a replication cohort, PCSK9 was quantitated in 1450 patients with GFR between 90 and 15 ml/min/1.73 m2 enrolled in the Ludwigshafen Risk and Cardiovascular Health Study (LURIC) that were prospectively followed for cardiovascular deaths. Results PCSK9 concentrations did not correlate with baseline GFR (CARE FOR HOMe: r = -0.034; p = 0.479; LURIC: r = -0.017; p = 0.512). 91 patients in CARE FOR HOMe and 335 patients in LURIC reached an endpoint during a median follow-up of 3.0 [1.8-4.1] years and 10.0 [7.3-10.6] years, respectively. Kaplan-Meier analyses showed that PCSK9 concentrations did not predict cardiovascular events in either cohort [CARE FOR HOMe (p = 0.622); LURIC (p = 0.729)]. Sensitivity analyses according to statin intake yielded similar results. Conclusion In two well characterized independent cohort studies, PCSK9 plasma levels did not correlate with kidney function. Furthermore, PCSK9 plasma concentrations were not associated with cardiovascular events in patients with reduced renal function.
Gesehen am 17.01.2019